The Troubled Nurse: A Qualitative Study of Psychoemotional Effects of Cancer Care on Nurses in A Nigerian Cancer Care Setting - Nwozichi, Chinomso Ugochukwu (Asia Pac J Oncol Nurs, 2020)
OBJECTIVE: Nurses who care for cancer patients are exposed to varying degrees of psychological pressure. These psychological issues among nurses are thought to have some consequences relating to professional satisfaction, quality of care, and patient outcome. This study aimed to explore the psychological and emotional impact of caring for persons among cancer care nurses. METHODS: A qualitative, descriptive approach was employed, and a purposive sampling technique was used to select seven nurses who were interviewed one-on-one. Interview data were coded and analyzed using NVivo 12 to generate the final themes and patterns. The EQUATOR's COREQ guideline for qualitative studies was adhered to. RESULTS: Data analysis yielded two major themes and four sub-themes. Participants expressed concerns about their frequent encounter with dying patients on the ward which affects their own mental well-being as persons. Sometimes, the health-care professionals used emotional distance to mitigate the emotional and psychological effects of the frequent deaths encountered on the ward. Professional dissatisfaction was also brought about by the increased amount of patients who died on the ward, the gloomy nature of the care environment, and the feeling of incapacitation to help. CONCLUSIONS: The findings indicate that nurses who care for cancer patients need to be supported to enhance their psychological and emotional well-being. The findings of this study could help nurse managers to understand the level of psychological pressure cancer care impose on nurses and the importance of improving the mental health of nurses in cancer care.